Suppressing the Initial Growth of Sidewall GaN by Modifying AlN-Coated Patterned Sapphire with KOH-Based Etchant. (1st January 2020) - Hsu, Wen-Yang; Kuo, Yen-Ting; Hung, Shang-Shih; Wu, Pei-Yu; Sheu, Jinn-Kong; Lin, Kun-Lin; Wu, YewChung Sermon
Abstract : Micron-sized patterned sapphire substrates (PSSs) with an ex situ sputtered AlN nucleation layer (NL) have been used to improve the performance of GaN-based light-emitting diodes (LEDs). The growth of GaN was enhanced not only from bottom c-plane, but also from the sidewall of the micron-sized patterns. In this study, KOH solution was used to etch AlN (especially sidewall AlN) for the first time. The additional etching process is very simple. It was found that KOH etching 1 min did enhance the light output power (LOP) of LED. However, with the increase of etching time to 4 min, the LOP decreased. Besides, the effect of remained AlN on GaN growth mechanism was investigated in detail.